Heat transfer characteristics of the flat plate integrated with metal foam of varying thickness using an unconfined circular air-jet impingement. (1st June 2023) - Kumar Singh, Pradeep; Joshi, Jaykumar; Sahu, Santosh Kumar
Highlights: Reports thermal performance of metal foam integrated plate with jet impingement. Effect of open-cell copper foam thickness on thermal performance is studied. Local and average Nusselt number is estimated for different foam thickness. Heat transfer correlations are proposed in terms of non-dimensional foam thickness. Thinner foam augments the heat transfer in the stagnation region. Abstract: The present study experimentally investigates the thermal performance of stainless-steel foil (AISI-304) integrated with copper open-cell metal foam (OCMF) of 10 pores per inch (PPI) and 90% porosity subjected to a circular air-jet impingement using thin foil thermal imaging technique. This investigation studies the stagnation, local, and average heat transfer characteristics of the foamed plate by varying the thickness of the OCMF in the jet flow directions. The effect of dimensionless thickness of OCMF ( t / d = 0.83, 1 and 1.16), dimensionless impinging distance ( z / d = 1.5, 2, 4, 6, 8 and 10), and Reynolds number ( Re = 10000 – 50000) is considered on the stagnation, local and average Nusselt number. The result shows that the presence of OCMF significantly improves the thermal performance of the surface. In addition, the surface with minimum OCMF thickness produces the highest enhancement in heat transfer. For the metal plate integrated with OCMF, the enhancement in the peak value of stagnation Nusselt number is found to be 56.1%, 86%, and 89% by varying the dimensionless foam thickness from 1.16 - 0.83 for Reynolds number 20000, 30000, and 40000, respectively. A correlation based on the experimental results is also proposed to determine the local Nusselt number in terms of dimensionless foam thickness, Reynolds number, dimensionless impinging distance, and dimensionless radial distance. This study provides essential guidelines for selecting OCMF for the foam-based heat sink.